2010
DOI: 10.1111/j.1467-8500.2010.00693.x
|View full text |Cite
|
Sign up to set email alerts
|

Retention Practices for Engineering and Technical Professionals in an Australian Public Agency

Abstract: Retaining employees with core business skills is a key human resources (HR) activity. This article examines retention of engineering and technical (E&T) professionals in an Australian public service agency by collecting data from 670 E&T professionals to compare attraction, retention and turnover intention by age and occupation. It was hypothesised that the influencers would vary by age, in line with the research on generational differences and employment patterns ( Chaminade 2005;Kyles 2005). This hypothesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Previous research has demonstrated that retention, whether in the private or public sector, is a multi-faceted construct that a number of drivers affect. They include employee commitment, especially affective and normative commitment (Abbott, White & Charles, 2005;Joseph, Ng, Koh & Ang, 2007;Meyer, Allen & Smith, 1993;Samuel & Chipunza, 2009), engagement (Dewhurst, 2009;Frank et al, 2004);communication (DeMarco, n.d.;Perrine, 2009); leadership and interaction (Dyer, 2009;Perrine, 2009;Samuel & Chipunza, 2009); and specific human resource (HR) practices (Bova & Kroth, 2001;Rose & Gordon, 2010;Samuel & Chipunza, 2009). Commitment and engagement correlate negatively with turnover or the intention to leave the organisation.…”
Section: Synthesis and Critical Evaluation Of The Literaturementioning
confidence: 99%
“…Previous research has demonstrated that retention, whether in the private or public sector, is a multi-faceted construct that a number of drivers affect. They include employee commitment, especially affective and normative commitment (Abbott, White & Charles, 2005;Joseph, Ng, Koh & Ang, 2007;Meyer, Allen & Smith, 1993;Samuel & Chipunza, 2009), engagement (Dewhurst, 2009;Frank et al, 2004);communication (DeMarco, n.d.;Perrine, 2009); leadership and interaction (Dyer, 2009;Perrine, 2009;Samuel & Chipunza, 2009); and specific human resource (HR) practices (Bova & Kroth, 2001;Rose & Gordon, 2010;Samuel & Chipunza, 2009). Commitment and engagement correlate negatively with turnover or the intention to leave the organisation.…”
Section: Synthesis and Critical Evaluation Of The Literaturementioning
confidence: 99%
“…Regarding the phenomenon of turnover among ICT professionals or mobile communications industry employees, there is a handful of published research; among these the works of Joseph and Ang (2003) On the other hand, regarding the application of fuzzy models in social, behavioral and management sciences, it should be admitted that they are not widely used for modeling problems of this kind; especially in the field of human resource management and organizational behavior, few studies have been conducted using these models. In fact, most of the papers seeking to explain the relationships or causal links among studied variables in these disciplines and particularly the issue of job turnover, use statistical techniques and especially structural equation modeling; for instance, in a research conducted by Robinson and Beesley (2010), regression analysis has been used to study the relationship between the variable of creativity and turnover intention; in another paper, Shim (2010) has used Logistic Regression Model (LRM) to study the relationship between organizational culture and atmosphere and empl turnover; In another research, Rose and Gordon (2010) have used ANOVA technique in order to study the relationship between the variables of gender and job type and the variable of staying in the organization; in a research, Yan and Zhou (2010) have used structural equation modeling to study the relationship among the factors affecting fear of turnover; in a research conducted by Zheng and Lamond (2009), multiple regression analysis has been used to examine the relationship between a number of variables and turnover in Asian multinational companies; and finally, in a research conducted by Mehregan & Seyed Kalali (2013b), factor analysis has been used to identify and classify the factors affecting turnover.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…The role of the line manager in creating conditions that encourage employee engagement cannot be overemphasised (Cheese et al 2008), especially in the case of Generation X employees (Ahlrichs, 2007;Cordeniz, 2002;Dewhurst, 2009, Dyer, 2009, Graen et al, 1982, Johnson, 2002Kaiser & Hogan, 2010;Perrine, 2009;Pfau & Kay, 2002;Rodriguez, Green & Ree, 2003;Rose & Gordon, 2010;Salopek, 2008;Wheeler et al, 2010). According to these authors factors influencing engagement include trust and integrity of leadership/the line manager, nature of the job, ability to align individual effort with organisational performance, career growth opportunities, pride in the organisation, relationships with co-workers, personal development and the relationship with the immediate manager.…”
Section: Employee Turnovermentioning
confidence: 99%
“…Generation Xers prefer leadership behaviours that are associated with generational themes, especially flexibility, recognition and challenging working conditions where they can use their skills (Cordeniz, 2002;Perrine, 2009;Pfau & Kay, 2002;Rodriguez et al, 2003;Salopek, 2008). Human resource (HR) practices valued by Generation X employees include flexible working arrangements in terms of working time, work and rewards (Cordeniz, 2002;Johnson, 2002;Rose & Gordon, 2010), recognition, including equitable pay (Ahlrichs, 2007;Perrine, 2009), training (including mentoring) and development, given that they are loyal to their skills (Ahlrichs, 2007;Cordeniz, 2002;Rose & Gordon, 2010;Ruch, 2000;Vaughn, 2008) and performance management (including feedback) (Rose & Gordon, 2010;Salopek, 2008;Schachter, 2009;Taylor, 2002;Vaughn, 2008). Generation Xers have no respect for service, title or rank, because their parents had it all but lost their jobs in any event (DeMarco, n.d.).…”
Section: Generation Xmentioning
confidence: 99%